Definition of CCS Provinces with Multi-criteria and Least Cost Path Analysis - Carneiro, Julio (2015)
The concept of CCS Provinces is introduced, referring to the region where a CO2 injection site is cost-effective based simultaneously on the cumulative transport and storage costs. The methodology implements, in a GIS tool, a linear cost model for pipeline construction considering local conditions that affect the pipeline cost. Multi-criteria analysis with those local factors, allows building cost surface maps representing the cost of a standardized diameter pipeline in any cell of the GIS model. The storage costs are assigned to the potential injection location and the resulting map is combined through map algebra with the transport cost surface. The CCS Province is defined using least cost path analysis to find for each cell in the GIS the lowest accumulative transport and storage cost and allocating to a given province all the cells that lead to the same storage site. The methodology is illustrated for the Iberian Peninsula and Morocco.